Personality Predicts Perception of Meaningful Stimuli During Binocular Rivalry - Aarnio, Jetta (My University, 2020)
Personality and its influence in visual perception have been of interest in many studies. One way to explore individual differences in perception of visual information is to use a binocular rivalry situation, where two markedly different stimuli are presented to each eye. This creates a rivalry situation, where one of the stimuli dominates aware perception while the perception of the other one is inhibited. During continuous viewing, the dominance starts to spontaneously alter between the images. Sometimes, if neither of them becomes fully inhibited or gains dominance, the perceived images can fuse into a mixed percept of them both. Many studies have found associations between various clinical conditions and the rate of alterations of the dominance, or prevalence of mixed percept. There are nevertheless very few studies about associations between personality and the temporal dynamics during binocular rivalry situation and no studies that would have explored associations between personality and rivalry dynamics by using meaningful stimuli. Using meaningful and also emotional stimuli could provide more information about the influence of top-down processes on perception during binocular rivalry. In the present study, I investigated whether personality traits or their facets predict perception in a binocular rivalry situation where participants were shown meaningful stimuli, such as faces with six different emotions and houses. The sample consisted of 100 university students. To address personality, I used a Finnish questionnaire PK5. I explored whether personality would predict the alteration rate of percepts or amounts and durations of perceiving mixed percepts, houses, faces, or faces and houses summed together during 10 s binocular rivalry trials. In this study Openness and Agreeableness predicted a higher alteration rate, a higher amount of reports of mixed percept and shorter durations of perceiving houses. Openness also predicted shorter durations of perceiving houses and faces summed together. When exploring if facets of Openness or Agreeableness would individually predict these rivalry variables, facet reflectivity of Openness predicted alteration rate and facet emotionality perceiving less of houses. The associations between Openness, its facets, and rivalry dynamics were partly expected based on previous research, but the associations between Agreeableness and rivalry dynamics were a new finding. These results suggest that personality influences perception during binocular rivalry when using meaningful stimuli. Because binocular rivalry could be used as a diagnostic tool in the future and it provides information about unconscious visual processing, it would be useful to do more research on the associations between personality and rivalry dynamics.
Keywords: PK5, persoonallisuus, binokulaarinen kilpailu